The Oxford handbook of early Christian apocrypha - Gregory, Andrew F. 1971- (Oxford Oxford University Press, 2015)
This handbook primarily focuses on issues and themes that arise in the study of early Christian apocrypha. Part one consists of authoritative surveys of the main branches of apocryphal literature (gospels, acts, epistles, apocalypses, and related literature) and part two considers key issues that they raise.
Keywords: Apocryphal books (New Testament) -- Criticism, interpretation, etc; Apocryphal books (New Testament) ; Criticism, interpretation, etc; Aufsatzsammlung